Conservación de chifles artesanales de plátano (Musa paradisiaca.) fritos en cuatro tipos de aceites de origen vegetal. - Rodríguez Castro, Rossy Lisbeth (2016)
In the present investigation examines the life of banana chips banana Elaborated artisan way, obtaining chemical and sensory analysis Finished. In the research project it is to understand the factors Process Influencing the lifetime of chifles Where we use three types of bananas such as the Dominico Harton and Barraganete, development of craft process is done within the UN Sensory Analysis, in which it specifies that the chifles They have a high acceptance in Consumer Very. Ecuador is very diverse A country both as tubers potato, cassava, carrot, sweet potato, applied to the Food Engineering Bananas, son Fruits More Consumed by its high potassium content. At present many of the so widely accepted Children, Youth and Adults Fried foods, son, because it is very fast and do look m Taste and are highly desired by people; for they also employ different types of oil to Get the Factors Influencing the Stability of banana chips, banana chips An evaluation of every 5 days was made, describing the organoleptic characteristics of rancidity (smell), taste, texture and color.